Amanah-Based Public Relations and Digital Trust in Islamic Private Universities - Aprianto, Iwan; Mawardi, Mawardi; Suparno, Suparno; Jamrizal (SCAD Independent, 2026)
Public trust has emerged as a critical challenge for Private Islamic Universities (PTIS) in the digital era, particularly regarding the translation of Islamic ethical values from symbolic claims into concrete institutional practices. This study examines how the value of Amanah (trust) is internalized within Public Relations (PR) practices at PTIS in Jambi, positioning trust as both a religious-ethical principle and a professional standard that guides governance, communication, and digital engagement. Using a qualitative multi-site case study design, data were collected through in-depth interviews with institutional leaders, PR personnel, academic staff, administrative officers, and students, complemented by observation of institutional digital platforms. Data were analysed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that Amanah functions as an internal governing logic, shaping leadership integrity, policy transparency, participatory communication, and digital accountability. Trust is further strengthened through inclusive leadership, open communication channels, transparent academic and administrative policies, and responsible digital governance. However, the study also identifies persistent challenges, including inconsistent leadership modelling, weak oversight mechanisms, limited digital literacy, and concerns regarding academic data security. These results indicate that ethical values alone are insufficient to sustain digital trust without structural reinforcement and accountable digital systems. Ultimately, this study contributes to the field by conceptualizing Amanah as an operational PR principle that integrates Islamic ethics with contemporary digital trust governance in higher education.